The Promotion Effect of Rural Sports Events on the Local Economic Development - Hu, Zijun; Wu, Zhen; Xie, Weiluo; Zhao, Jianye (Transactions on Economics, Business and Management Research, 2024)
The Village BA model, which originated in Taipan Village, Guizhou, China, offers an innovative framework for rural economic development through the strategic implementation of sports events. This model focuses on several key areas: first, it advocates for significant investment in rural infrastructure, which includes improving facilities that cater to both locals and tourists. Second, it emphasizes the enhancement of visitor reception standards to create a welcoming atmosphere. Additionally, the development of a strong event brand is crucial for attracting tourists and investors alike, which in turn stimulates economic growth. The model also highlights the need for robust policy support, specialized training programs, and ongoing infrastructure improvements, ensuring that it can be successfully replicated in other rural areas. Moreover, fostering community engagement and promoting collaboration across various sectors are essential for the sustainability and long-term success of these initiatives. Ultimately, the Village BA model has the potential to deliver substantial economic benefits and enduring prosperity to rural communities.